Transplants today and tomorrow - Dudley, H. A. F. (Hugh Arnold Freeman), 1925- (1968)
A talk given to the Monash University Association by Hugh Dudley, Professor of Surgery.
Manuscript reference no. : NLA MS 2694.
Keywords: Transplantation of organs, tissues, etc; Surgeons